THE BIG FIVE PERSONALITY DAN KEBAHAGIAAN SUKU BALI - Narosaputra, Dewo Agung Nugroho; Kaunang, Sinta Elisa Jelita; Wantah, Mario Erick (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Culture is an important influence on people in looking at happiness. Especially balinese culture that is rich in teachings in expressing culture. Happiness depends on how a human evaluates himself or herself that is influenced by a person's personality. This research aims to find out the relationship of Big five personality with happiness, the relationship between extraversion and happiness, the relationship between agreeableness and happiness, the relationship between neuroticism and happiness, the relationship between Openness to Experience and happiness, the relationship between conscientiousness and happiness. This study used quantitative methods with a sample of 32 people from majapahit balinese tribe. The data collection of this study used the Big Five Inventory scale with dimensions Extraversion, Agreeableness, Conscientiousness, Neuroticism, Openness to Experience and the second Oxford Happiness Scale. The results of this study show that there is a positive and significant relationship between The Big five personality and 4 dimensions (Extraversion, Agreeableness, Conscientiousness, Openness to Experience) with the happiness of balinese people. Meanwhile, in personality neuroticism there is no significant relationship with happiness. Happiness has its own characteristics based on the culture embraced in balinese people. Further discussions will be presented in the entire article.